Harnessing the nutraceutical properties, Microbial composition of scarabaeoid beetle Larvae and antibacterial compounds of its Endozoic fungus (aspergillus welwitschia) - MWANZA, SYLVIAH SYOMBUA (Sylviah Syombua Mwanza, 2024)
The systematic development of antibiotic resistance poses huge worldwide health challenges, specifically in low- and middle- income countries (LMICs) increasing the treatment costs. There is heightened need to broaden the search for new antibiotic sources such as exploration of insects beyond soil microorganisms. Insects harbor symbiotic microbes in their guts which can be utilized in developing effective antimicrobial agents. However, entomophagy is the main activity associated with edible insects leaving a paucity of knowledge on their therapeutic benefits. Further, very few researches have been done to understand the microbial composition of comestible insects. This research focused on exploring novel functional properties and characterizing the associated microbiota from the gut of two scarabaeoid larvae collected from Embu, Murang’a and Nairobi counties. Further, the culturable fungal organisms were investigated for their antibacterial potency. The larvae were dissected to obtain the gut portions then pooled and divided into two proportions. One part was used for culturing the fungal isolates and the other was used to obtain DNA for metagenomics analysis. The degutted body remains were used for nutritional profiling. Bioassay-guided isolation was carried out to obtain the bio-active compounds whose structures were elucidated using spectroscopic techniques. The most bioactive fungus was identified using Sanger sequencing targeting the Internal Transcribed Spacer (ITS) gene. The larvae were identified using morphological features and molecular tools as Cetonia aurata and Oryctes rhinoceros. They were also found to be excellent sources of both macro [44% for O. rhinoceros and 63% for C. aurata] and micronutrients calcium (20.42–22.65 mg/g) and zinc minerals (0.28–0.3 mg/g). The dominant bacterial communities in their gut were Firmicutes (42.10%) and Bacteroidota (32.50%) for C. aurata, while O. rhinoceros was dominated by Proteobacteria (35.00%), Actinobacteriota (11.40%), and Desulfobacterota (7.40%). The fungal community was represented by the class Lecanoromycetes (92.60%) in O. rhinoceros, whereas Saccharomycetes (92.60%) prevailed in C. aurata. This work uncovered possible microbiota functions to include the generation of biosynthetic intermediates necessary for anabolic and catabolic activities, adaptive metabolism and energy production. The screening antibacterial results revealed that the most active mixed fungal extract originated from dung beetle larvae in Murang'a. Sub-culturing yielded to the 15 axenic strains. Antibacterial assays identified the most active strain to be Aspergillus welwitschia, with ethyl acetate fraction displaying the highest activity against the tested bacterial strains. Rubasperone B and rubrofusarin B were successfully isolated from this fraction and linked to the observed antibacterial activity. These findings indicate that the Scarabaeoid beetle larvae are endowed with macronutrients and entomochemicals that could find application in fortifying food and feed substances. Additionally, the predicted functions of the gut microbiota provide a theoretical framework for biotechnological uses in waste management and bio-functional foods. In pharmacology, the characterized compounds are significant in the development of new medications to help combat the impacts of Multi-Drug Resistant (MDR) bacteria and contribute to the accomplishment of the UN Sustainable Development Goals (SDGs) chiefly SDG 3 on well-being and good health.
Thesis